The Effect of Accrual Heterogeneity on Accrual Quality Inferences - Dechow, Patricia M.; Larson, Chad R.; Resutek, Robert J. (The Accounting Review, 2022)
ABSTRACT We investigate the impact of the mixed attribute GAAP measurement model on accrual quality inferences. GAAP rules vary from an income statement “matching” focus to a balance sheet “fair-value” focus. Accrual properties are also affected by the business activity being measured and the activity's recurrence. Furthermore, accrual measurement is affected by managerial estimation error/manipulation. As a consequence, accruals are heterogeneous with predictably different statistical properties. We construct a dataset of more than 100,000 accrual items that Compustat aggregates into data item FOPO. We classify these accruals into 32 types over a 21-year span. We show that variation in persistence for the 32 accrual types is consistent with our predictions concerning GAAP rules. We provide a model of accruals and show that it is implausible for estimation error of reasonable magnitudes to explain this variation. Finally, we develop a measure of reporting consistency and show its impact on accrual quality inferences.